0BB precision link welding strip packaging film and preparation method thereof
By introducing a bonding layer with low fluidity and low water vapor transmission into the packaging film, the problem of poor shaping effect of existing films on welding tape is solved, and precision links of welding tapes and high yield and reliability of battery components are achieved.
Patent Information
- Application Number
- CN202310196337.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-03
AI Technical Summary
The existing packaging films have poor shaping effect on welding tape, resulting in an increased risk of welding tape false joints, affecting the yield and reliability of battery components.
An OBB precision link welding tape encapsulation film is employed, which includes a film layer and a bonding layer with low fluidity and low water vapor transmittance after UV curing. The bonding layer is printed on the adhesive film by roll coating and irradiated in line with UV to obtain low flowability and proper adhesion.
This film can effectively coat and shape the 0BB welding tape, avoid poor bonding between the welding tape and the battery cell, improve the yield and reliability of the components, and avoid the impact of new batteries on water vapor corrosion.
Smart Images

Figure CN116285713B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of packaging films, and in particular relates to an 0BB precision link welding strip packaging film and a preparation method thereof. Background Art
[0002] There are endless solutions for the new type of battery busbar-free 0BB packaging, the purpose of which is to make the carrier film have low fluidity to achieve the shaping effect of the welding strip. The current direction is to use inorganic / organic mesh film as the carrier layer, the advantage is that the lamination does not flow, and the transmittance needs to be sacrificed; the split film carrier layer uses low melting point and high melting point resin to reduce fluidity, but the disadvantage is that the laying of low-weight split-carrier film is more difficult and the cost is increased; there is also the method of reducing the fluidity of the integrated film by EB / UV irradiation, the disadvantage is that the peeling force of the overall resin on the battery cell or glass is seriously reduced after irradiation. Summary of the invention
[0003] The present invention provides a 0BB precision link solder strip packaging adhesive film and a preparation method thereof, so as to solve the technical problem that the existing packaging adhesive film has a poor shaping effect on the solder strip.
[0004] In order to solve the above technical problems, the present invention provides a 0BB precision link welding tape packaging film, comprising: a film layer and a bonding layer located on one side thereof; wherein the bonding layer has low fluidity after UV curing, and the torque is 0.50-2.0 dN·m at 100°C; 0.25-1.0 dN·m at 145°C; the water vapor permeability of the bonding layer is ≤5g / (m 2 · 24h); after lamination, the bonding layer covers and shapes the solder strip having one side bonded and fixed to the battery.
[0005] On the other hand, the present invention also provides a method for preparing a 0BB precision link weld tape packaging film, comprising the following steps: step S1, respectively mixing the raw materials of the photovoltaic film and the raw materials of the bonding layer and adding them to the extruder for casting; step S2, printing the bonding layer on the photovoltaic film by roll coating, and obtaining the 0BB precision link weld tape packaging film as described above after online UV irradiation.
[0006] The beneficial effect of the present invention is that the present invention is optimized on the basis of the original photovoltaic adhesive film: the adhesive film layer is obtained by roll-coating printing to obtain a bonding layer, which can cover the 0BB welding strip, and the bonding layer uses a resin with low water vapor permeability and has no acidic group in the structure, thereby avoiding the influence of water vapor corrosion on the new battery; and the light transmittance and adhesion of the adhesive film itself do not change. The encapsulation adhesive film can precisely connect the welding strip, avoid the risk of power reduction of the component with virtual connection of the welding strip, and further improve the yield and reliability of the component.
[0007] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practicing the present invention.
[0008] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0010] Figure 1 It is a shaping effect diagram of the 0BB precision link welding strip packaging film of the present invention. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] The present invention provides a 0BB precision link welding tape packaging adhesive film, comprising: an adhesive film layer and a bonding layer located on one side thereof; wherein the bonding layer has low fluidity after UV curing, and the torque is 0.50-2.0 dN·m at 100°C; 0.25-1.0 dN·m at 145°C; the water vapor transmission rate of the bonding layer is ≤5g / (m 2 · 24h); after lamination, the bonding layer covers and shapes the solder strip having one side bonded and fixed to the battery.
[0013] Specifically, the bonding layer after UV curing has low fluidity. The lamination process bonds the solder ribbon to the battery cell, preventing the adhesive film from flowing between the solder ribbon and the battery cell. The resin with low water vapor permeability also avoids the impact of water vapor corrosion on the new battery.
[0014] In this embodiment, specifically, the thickness of the laminating layer is 5-80 μm. Within this thickness range, UV light can penetrate and cure. If the thickness is greater than 80 μm, it will affect the penetration of UV light, thereby causing the residue of photoinitiator.
[0015] In this embodiment, specifically, the viscosity of the laminating layer is 100-2000 mPa.s at 25° C. The viscosity of the laminating layer affects the roller coating process and is also related to the thickness of the coating.
[0016] In this embodiment, specifically, the mass fractions of the components in the bonding layer are: 17-57.5 parts of polyurethane acrylate; 15-25 parts of monofunctional and difunctional reactive diluents; 20-35 parts of trifunctional and tetrafunctional reactive diluents; 2-6 parts of photoinitiator; 0.5-2 parts of coupling agent; and 5-15 parts of filler.
[0017] In this embodiment, specifically, the preparation method of the polyurethane acrylate includes: reacting polypropylene glycol diol or polytetramethylene glycol diol with diisocyanate to obtain an isocyanate polyurethane oligomer with an end group, and then capping it with a monofunctional acrylate to obtain polyurethane acrylate; wherein the monofunctional acrylate includes: hydroxyethyl methacrylate or hydroxyethyl acrylate, hydroxypropyl methacrylate and hydroxypropyl acrylate, with a mass ratio of 1:2:2; and the reaction temperature is 75-80°C; the reaction time for each stage is 2h.
[0018] Specifically, a resin with low water vapor permeability and no acidic groups in the structure is selected to avoid the influence of water vapor corrosion on the new battery.
[0019] In this embodiment, specifically, the trifunctional and tetrafunctional reactive diluents include: triallyl isocyanurate (TAIC), (ethoxylated / propoxylated) trimethylolpropane triacrylate, propoxylated pentaerythritol acrylate, any one or more thereof; the trifunctional and tetrafunctional reactive diluents have high reactivity and can adjust the curing rate; the difunctional reactive diluents include: 1,6-hexanediol diacrylate (HDDA), difunctional tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), neopentyl glycol diacrylate (NPGDA), any one or more thereof; the monofunctional reactive diluents include: isobornyl acrylate, hydroxyethyl methacrylate / hydroxypropyl methacrylate, isooctyl acrylate, any one or more thereof; the monofunctional and difunctional reactive diluents have the effect of adjusting the viscosity and adhesion of the system.
[0020] In this embodiment, specifically, the photoinitiator includes: 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 1-hydroxy-cyclohexyl phenyl ketone (184), 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone (907), dimethyl benzoate (DMPA), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), benzophenone (BP), 2-isopropylthioxanthone (ITX), camphorquinone (CQ) Any one or more.
[0021] In this embodiment, specifically, the coupling agent includes: one or more of mercaptosilane, isocyanate silane and double bond silane; wherein the mercaptosilane includes: any one or more of SH-PEG-Silane mercapto polyethylene glycol silicon, mercapto silicone oil and 3-mercaptopropyl trimethoxy silane; wherein the structural formula of the SH-PEG-Silane mercapto polyethylene glycol silicon is
[0022] The isocyanate silane includes: 3-isocyanate propyl trimethyl (ethyl) silane; the double bond silane includes: acryloxy and vinyl silane; the coupling agent can provide the peeling force between the packaging film and the welding tape.
[0023] In this embodiment, specifically, the filler includes a thixotropic agent and an anti-aging agent; wherein the thixotropic agent includes any one or more of hydrogenated castor oil, attapulgite and nano-silicon dioxide; and the anti-aging agent includes any one or more of nano-zinc oxide and nano-titanium dioxide.
[0024] The present invention also provides a method for preparing a 0BB precision link welding tape packaging film, comprising the following steps: step S1, respectively mixing the raw materials of the photovoltaic film and the raw materials of the bonding layer and adding them to the extruder for casting; step S2, printing the bonding layer on the photovoltaic film by roll coating, and obtaining the 0BB precision link welding tape packaging film as described above after online UV irradiation.
[0025] Specifically, the casting rate in step S1 is 2-10 m / min.
[0026] Specifically, in step S2, the online UV uses a low-frequency electrodeless lamp, and two models of 250KHz and 140KHz are selected, with a wavelength range of 254nm-365nm, a light efficiency of 5Lm / W, a power range of 20-400W, and a light intensity of 50-1000mW / cm.
[0027] Example 1
[0028] Example 1 provides a 0BB precision link solder strip packaging film and a preparation method thereof, the only difference being that the components and amounts of the bonding layer are different, and there is no mercapto and isocyanate silane. The viscosity of the system is 680 mPa.s., and the thickness after curing is 35 μm.
[0029] The formula composition of the bonding layer in this embodiment is: 36.5 parts of polyethylene glycol / hydrogenated HMDI diisocyanate-urethane acrylate prepolymer, 20 parts of pentaerythritol triacrylate, 10 parts of neopentyl glycol diacrylate (NPGDA) and 15 parts of hydroxyethyl methacrylate; 3 parts of photoinitiator 184, 0.5 parts of methacryloyloxypropyl trimethoxysilane, 10 parts of attapulgite, and 5 parts of nano zinc oxide.
[0030] Example 2
[0031] Example 2 provides a 0BB precision link solder strip packaging film and a preparation method thereof, the only difference being that the components and amounts of the bonding layer are different. The viscosity of the system is relatively high at 1200 mPa.s., and the thickness after curing is 60 microns.
[0032] Preparation of the polyurethane acrylate prepolymer of the laminating layer of this embodiment: polytetrahydrofuran diol (400g / mol) was devacuated at 100°C for 1h and then cooled to 70°C, and two times the mole of hexamethylene diisocyanate HDI was slowly added to react for 0.5h, and the temperature was raised to 80°C and continued to react for 1.5h, and then cooled to 50°C and the same molar amount of hydroxyethyl methacrylate was added to seal for 2h to obtain 48 parts of the prepolymer; then 20 parts of triallyl isocyanurate (TAIC) active diluent, 5 parts of 1,6-hexanediol diacrylate (HDDA) and 5 parts of isobornyl acrylate were added in sequence; 2 parts of photoinitiator, 0.2 parts of mercapto polyethylene glycol silicon, 0.5 parts of 3-isocyanate propyl triethoxy silane, 0.3 parts of vinyl trimethoxy silane, 12 parts of nano silicon dioxide OK520 and 3 parts of nano titanium dioxide were added as coupling agents.
[0033] Example 3
[0034] Example 3 provides a 0BB precision link solder strip packaging film and a preparation method thereof, the difference being that the components and dosage of the bonding layer are different, which is reflected in the lower viscosity of 200mPa.s. and the curing time of 30s. The thickness of the bonding layer after curing is 15 microns.
[0035] The formula composition of the bonding layer in this embodiment is: 29.5 parts of polypropylene glycol / isophorone IPDI diisocyanate-urethane acrylate prepolymer, 25 parts of trifunctional ethoxylated TMPTMA, 15 parts of tripropylene glycol diacrylate (TPGDA) and 10 parts of isooctyl acrylate; 4 parts of photoinitiator, 0.5 parts of 3-mercaptopropyltrimethoxysilane, 0.5 parts of 3-isocyanatepropyltrimethoxysilane, 0.5 parts of methacryloxytrimethoxysilane as coupling agents, 10 parts of nano-silica A200F and 5 parts of nano-zinc oxide.
[0036] Comparative Example 1: No lamination layer, conventional high cutoff adhesive film, its transmittance at 280-380nm is ≤20%, avoiding UV light damage to the ITO layer of the heterojunction cell.
[0037] Table 1 Test results of packaging films of Examples 1-3 and Comparative Example 1
[0038]
[0039] Shaping effect: Sample preparation: Take the encapsulation film samples prepared in Examples 1-3 and Comparative Example 1, and put them into a laminator according to the order of "release film / film sample / HJT cell + solder tape fixed by positioning tape / film sample / release film". The lamination parameters are 145°C, extraction for 5 minutes, and lamination for 11 minutes. Cut a section of it, cure it with epoxy resin, polish it, and observe the cross section with a metallographic microscope.
[0040] Acid value test: The determination of free acetic acid content in EVA film can be generally divided into two steps: 1) acetic acid dissolution; 2) acetic acid content determination. Acetic acid dissolution, the laminated film is subjected to wet heat aging. Ultrasonic dissolution of a mixture of ethanol and water. Acetic acid content determination, the free acetic acid is neutralized by titration with potassium hydroxide solution, and the dissolved acetic acid content can be tested. Phenolphthalein indicator is added to potassium hydrogen phthalate solution to calibrate KOH solution.
[0041] Peel strength with HJT cell: Sample preparation, take the encapsulation film samples prepared in Examples 1-3 and Comparative Example 1, and put them into the laminator in the order of "embossed glass / Comparative Example 1 film sample / HJT cell / double-sided release film / Examples 1-3 and Comparative Example 1 film / KPC backplane" according to the test method of GB / T 29848-2018, and laminator with lamination parameters of 145°C for 5min and 11min. Among them, the double-sided release film is spaced 1cm apart on the surface of the HJT battery, and a 12cm long gap is provided to ensure that the encapsulation film contacts the cell with several strips of 1cm width. Using a CMT2203 universal electronic stretching machine, and according to the experimental steps specified in GB / T 2790-1995, the stretching speed is 100mm / min, and the arithmetic average of 3 parallel tests is taken to obtain the peel strength between the barrier layer of the encapsulation film sample and the HJT cell.
[0042] like Figure 1 As shown, the comparative example 1 produced a virtual connection, and the resin of the adhesive film of the comparative example 1 flowed into the soldering strip and the battery cell during the lamination process; the adhesive films of the examples 1, 2 and 3 had a good shaping effect on the soldering strip, and the solder on the soldering strip melted and bonded to the battery.
[0043] In summary, the present invention is optimized on the basis of the original photovoltaic adhesive film: the adhesive film layer is obtained by roll-coating printing to obtain a bonding layer, which can cover the 0BB welding strip, and the bonding layer uses a resin with low water vapor permeability and has no acidic groups in the structure, which avoids the influence of water vapor corrosion on the new battery; and the light transmittance and adhesion of the adhesive film itself do not change. The encapsulation adhesive film can precisely connect the welding strip, avoiding the risk of power reduction of the component with virtual connection of the welding strip, and further improving the yield and reliability of the component.
[0044] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A 0BB precision link welding strip packaging film, characterized in that: include: An adhesive film layer and a laminating layer located on one side thereof; in The laminating layer has low fluidity after UV curing, and the torque is 0.50-2.0 dN·m at 100°C; 0.25-1.0 dN·m at 145°C; The water vapor transmission rate of the laminating layer is ≤5 g / (m 2 24h); The bonding layer covers and shapes the solder strip whose one side is bonded and fixed on the battery after lamination; The mass fractions of each component in the laminating layer are: Polyurethane acrylate 17-57.5 parts; 15-25 parts of monofunctional and difunctional reactive diluents; 20-35 parts of tri-functional and tetra-functional reactive diluents; 2-6 parts of photoinitiator; Coupling agent 0.5-2 parts; 5-15 parts of filler; The preparation method of the polyurethane acrylate comprises: The polypropylene glycol diol or polytetramethylene glycol diol is reacted with diisocyanate to obtain a polyurethane oligomer having an isocyanate terminal group, which is then capped with a monofunctional acrylate to obtain a polyurethane acrylate; The monofunctional acrylate comprises: hydroxyethyl methacrylate or hydroxyethyl acrylate, hydroxypropyl methacrylate and hydroxypropyl acrylate, with a mass ratio of 1:2:2; and The reaction temperature is 75-80°C; The reaction time for each stage was 2 h.
2. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The thickness of the laminating layer is 5-80 μm.
3. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The viscosity of the laminating layer is 100-2000 mPa.s. at 25°C.
4. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The trifunctional and tetrafunctional reactive diluents include any one or more of triallyl isocyanurate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, and propoxylated pentaerythritol acrylate; The difunctional reactive diluent includes any one or more of 1,6-hexanediol diacrylate, difunctional tripropylene glycol diacrylate, dipropylene glycol diacrylate, and neopentyl glycol diacrylate; The monofunctional active diluent includes any one or more of isobornyl acrylate, hydroxyethyl / hydroxypropyl methacrylate, and isooctyl acrylate.
5. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The photoinitiator includes any one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl phenyl ketone, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, benzoin dimethyl ether, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzophenone, 2-isopropylthioxanthone, and camphorquinone.
6. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The coupling agent includes: one or more of mercaptosilane, isocyanate silane and double bond silane; wherein The mercaptosilane includes any one or more of SH-PEG-Silane mercaptopolyethylene glycol silicon, mercapto silicone oil and 3-mercaptopropyltrimethoxysilane; wherein The structural formula of the SH-PEG-Silane mercapto polyethylene glycol silicon is ; The isocyanate silane includes: 3-isocyanate propyl trimethyl (ethyl) oxysilane; The double bond silane includes: acryloxy and vinyl silane.
7. The 0BB precision link welding tape packaging film according to claim 1, characterized in that: The filler includes a thixotropic agent and an anti-aging agent; wherein The thixotropic agent includes any one or more of hydrogenated castor oil, attapulgite and nano-silicon dioxide; The anti-aging agent includes any one or more of nano zinc oxide and nano titanium dioxide.
8. A method for preparing the 0BB precision link welding tape packaging film according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, mixing the raw materials of the photovoltaic film and the raw materials of the laminating layer respectively and adding them into an extruder for casting; Step S2, the bonding layer is printed on the photovoltaic film by roll coating, and after online UV irradiation, the 0BB precision link welding tape packaging film as described in claim 1 is obtained.
Citation Information
Patent Citations
Packaging adhesive film and preparation method and application thereof
CN114921187A
Packaging adhesive film for heterojunction battery and preparation method and application of packaging adhesive film
CN114958216A